Increasing Children's Empowerment through Daily Work Habits at Home (Chores) for Optimizing Child Growth and Development - Hardika Hardika; Eny Nur Aisyah; Tomas Iriyanto (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to describe the strategies of parents to improve children's empowerment through the habit of doing daily work at home (chores) to optimize child growth and development. This research is focused on children aged 4-5 years. This type of research is a case study using an ethnomethodology qualitative approach. The focus of the research was conducted in two young households with parents background as a government employee and parents with the background as household assistants. The main data sources in this study are the parents of children, household assistants, and children concerned. Data is collected through in-depth interviews and observations in the child's home environment. Data analysis was performed using interactive analysis techniques, through phasing (1) selecting and sorting information, (2) elaboration of information, and (3) verifying information and (4) summarizing research findings. The results showed that there were different strategies and different achievement targets in developing children's empowerment through habituation of daily work at home for young families with job backgrounds as government employee and family a background as household assistant. AbstrakThis study aims to describe the strategies of parents to improve children's empowerment through the habit of doing daily work at home (chores) to optimize child growth and development. This research is focused on children aged 4-5 years. This type of research is a case study using an ethnomethodology qualitative approach. The focus of the research was conducted in two young households with parents background as a government employee and parents with the background as household assistants. The main data sources in this study are the parents of children, household assistants, and children concerned. Data is collected through in-depth interviews and observations in the child's home environment. Data analysis was performed using interactive analysis techniques, through phasing (1) selecting and sorting information, (2) elaboration of information, and (3) verifying information and (4) summarizing research findings. The results showed that there were different strategies and different achievement targets in developing children's empowerment through habituation of daily work at home for young families with job backgrounds as government employee and family a background as household assistant.